Urbefolkningars exklusion inom hållbar utveckling : En jämförande diskursanalys om maktrelationen mellan inhemska och västerländska kunskaper i en dominant kunskapsdiskurs om ekologisk hållbarhet - Hellgren Nilsson, Aemelia (Karlstads universitet, Institutionen för sociala och psykologiska studier (from 2013), 2020)
This paper seeks to understand how indigenous knowledge tends to be excluded in a global dominant Western discourse of knowledge. Indigenous people have due to European colonialism, racism and power been structurally marginalized and oppressed for centuries. Hence, social ideas and practices about Western knowledge have emerged as more legitimate than any other form of knowledge. Using discourse analysis as a method, I do investigate various articles from Western, American Native and Sami people newspapers. The purpose is to visualize their power relationship and perceptional differences of ecological sustainability. By analyzing their choices of words in the articles, I interpret their attitudes and put them in a broader societal context trough sociological and postcolonial theoretical contributions. The scholars I use are Foucault, Mannheim, Laclau & Mouffe and Said. Therefore, this paper explains the Western dominance in the discourse of knowledge as a product of social practices in terms of power, discourses and postcolonialism, rather than an objectifying scientific truth. Consequently, this can hopefully display other contributions of solutions from indigenous knowledge to contemporary issues our world is facing. Thus, my thesis problematizes how the exclusion of indigenous knowledge in the dominant discourse of knowledge negatively can affect ecological sustainability in terms of dismissed additional indigenous solutions. The purpose is to create bigger hybridity with a diversity of ideas, creativity and contributions to sustainable development. I argue that Western legitimacy is just an idea hanging on long social processes of discourses, power and social constructions of the reality. By clarifying this phenomenon with empirical shreds of evidence, I hope to contribute with new understandings about the marginalized position indigenous knowledge possess and amplify indigenous discourse in the dominant Western discourse of knowledge.